Global methylation correlates with clinical status in multiple sclerosis patients in the first year of IFNbeta treatment. - Pinto-Medel, Mª Jesús; Oliver-Martos, Begoña; Urbaneja-Romero, Patricia; Hurtado-Guerrero, Isaac; Ortega-Pinazo, Jesús; Serrano-Castro, Pedro Jesús; Fernández-Fernández, Óscar; Leyva-Fernández, Laura (Nature, 2017)
The alteration of DNA methylation patterns are a key component of disease onset and/or progression. Our objective was to evaluate the differences in Long Interspersed Nuclear Element-1 (LINE-1) methylation levels, as a surrogate marker of global DNA methylation, between multiple sclerosis (MS) patients and healthy controls. In addition, we assessed the association of LINE-1 methylation with clinical disease activity in patients treated with IFNbeta (IFNβ). We found that individuals with high levels of LINE-1 methylation showed 6-fold increased risk of suffering MS. Additionally, treated MS patients who bear high LINE-1 methylation levels had an 11-fold increased risk of clinical activity. Moreover, a negative correlation between treatment duration and percentage of LINE-1 methylation, that was statistically significant exclusively in the group of patients without clinical activity, was observed. Our data suggest that in MS patients, a slight global DNA hypermethylation occurs that may be related to the pathophysiology of the disease. In addition, global DNA methylation levels could play a role as a biomarker for the differential clinical response to IFNβ.
Keywords: Esclerosis múltiple - Tratamiento; Metilación; Biología molecular; multiple sclerosis; methylation; LINE-1; clinical response to IFN beta